Enigmatic Deep-Water Mounds on the Orphan Knoll, Labrador Sea - Meredyk, Shawn P.; Edinger, Evan; Piper, David J. W.; Huvenne, Veerle A. I.; Hoy, Shannon; Ruffman, Alan (Frontiers in Marine Science, 2020)
Deep-sea mounds can have a variety of origins and may provide hard-substrate features in depths that are normally dominated by mud. Orphan Knoll, a 2 km high bedrock horst off northeast Newfoundland, hosts more than 250 mounds of unknown composition, 10-1000 m high and 1-3 km wide in water depths of 1600–3200 m. The study objective was to characterize the size, shape, orientation, and composition of the enigmatic Orphan Knoll mounds, in order to determine their age and origin. Archival ship-based side-scan sonar, multibeam sonar, airgun, high-resolution sparker and 3.5 kHz acoustic sub-bottom profiling, and newly acquired ship-based multibeam sonar, video transects by remotely operated vehicle (ROV), rock samples, and near-bottom multibeam sonar data were analyzed. Four mounds were studied during two ROV dives. Archival sidescan sonar data show >200 mounds. Sparker profiles show that the mound crests are covered by condensed stratified Quaternary sediment and airgun seismic data show faults reaching near the seafloor. New multibeam sonar data show mounds are dominantly conical to elliptical in shape, but without preferred orientation or alignment. ROV transects and near-bottom multibeam showed that three mounds were rounded and symmetrically arranged, while a fourth was more asymmetrical, with steep faces on the southwestern and southeastern flanks, where finely bedded to massive sedimentary bedrock outcropped dipping 15-45°SW. Rock samples from the mounds include Eocene calcareous ooze and mid-Miocene bedded pelagic limestone. Thick ferromanganese crusts were found on many surfaces, obscuring possible outcrops from physical sampling. Polymetallic nodules were found on the slope of one mound. Ice-rafted detritus, including igneous and metamorphic rocks and Paleozoic limestone and dolostone, was common in the sediments immediately surrounding the mounds. Quaternary sub-fossil solitary scleractinian corals accumulated over a span of at least 0.18 Ma at the base of one mound. The presence of uplifted condensed Eocene-Miocene rocks on the mounds and faulting in seismic profiles suggest uplift during reactivation of old rift-related faults during the Neogene, with seabed mass wasting creating residual mounds, which were then draped by Quaternary proglacial muds. Sculpting of hemipelagic Quaternary sediment by bottom currents probably contributed to mound morphology.